Effect of seedling age, seeding density and nitrogen fertilizer on growth and grain yield of rice (Oryza sativa L.) - Saroj Thapa; Khagendra Thapa; Jiban Shrestha; Amit Chaudhary (Hasanuddin University, 2019)
Rice (Oryza sativa L.) is first staple crop of Nepal. The national average yield of rice is less than its potential yield, for which poor agronomic management has been reported as the critical factor. Among various agro-management practices seedling age, seeding density and nitrogen rates significantly affect the growth and yield of rice. The lower seeding density produces the taller plant, more effective tiller, lower sterility and higher grain yield. On the other hand, seedling of older age from higher seeding density gives the lowest yield. Transplanting younger seedling with low seeding density and application of recommended dose of nitrogen gives a higher yield. This article summarizes various effects of seedling age, seeding density and nitrogen rates on plant height, number of effective tillers, number of filled grains, thousand grain weight and grain yield of rice. This information may be useful for maize growers and researchers.